Mesenchymal stem cell (MSc) secretome: A possible therapeutic strategy for intensive-care COVID-19 patients - Deffune, Elenice [UNESP]; Prudenciatti, Aruã [UNESP]; Moroz, Andrei [UNESP] (Elsevier, 2020)
As an emerging global health challenge, COVID-19 requires international knowledge to reach novel possible therapeutic strategies, especially for intensive-care patients. During the early stages of infection, pneumocytes II are the primary infected cells, harming the respiratory system. We have previous evidence in murine models that MSc's secretome can be used to treat pulmonary injuries induced with bleomycin, due to its content: growth factors, extracellular vesicles, and exosomes. We hypothesize and strongly recommend MSc secretome testing and production, in xenofree conditions, to be used as an alternative approach in SARS-Cov-2 patients in critical conditions.
Keywords: COVID-19; MSc secretome; Novel strategy